Improved message authentication technique on IEEE 802.15.4 wireless sensor network using multiple key protocol - Al-Alak, Saif M. Kh. (2014)
Wireless communication is utilized for transferring data over nodes. The Wireless Sensor Network (WSN) is defined to connect the sensors by using a set of protocols. The IEEE 802.15.4 standard includes the required protocols to construct a WSN. The security protocols of the IEEE 802.15.4 support the protection for the WSN; however, the implement of security protocols degrades the performance of the WSN. Also, the encryption system limits the size of the transferred message, since it adopts a single secret key for message ciphering that leads to the possibility of key attack. The authentication algorithm of IEEE 802.15.4 has constraints on a multi processor system, since it can work only in sequential fashion. The aim of the study is to reduce the delay of the authentication operation in WSN and to reduce the possibility of general attack on the ciphertext message in WSN. In this study, the pretest-posttest design is implemented along with the research tests. The implementation of the MKP in the IEEE 802.15.4 WSN increases the flexibility of the cipher transferred message according to the number of secret keys, where each secret key may be used to encrypt 261 blocks (each block is 16-octet) that leads to the increase in the flexibility of the message size. Meanwhile, the complexity of the secret key is increased, since the number of a mathematical operations to break the secret key is duplicated according to the number of secret keys. Also, the MKP increases the randomness of the ciphertext message, since the message is encrypted with distinct secret keys. Furthermore, the MKP increases the resistance of the ciphertext message against attacks. The DMAC algorithm increases the system utilization for the IEEE 802.15.4 WSN. The DMAC authenticates the messages’ block in parallel fashion by utilizing the available processing units. The time of message authentication operation in the IEEE 802.15.4 WSN is decreased by DMAC. The study shows that the developed algorithms MKPAES and DMAC increase the performance of the WSN and improve the system resistance to attacks on the WSN. The increase of system performance of the WSN improves the efficiency of the WSN. The improvement of the security system of the WSN makes it more trustworthy.